Dayah Entrepreneur dan Budaya Akademis Santri: Pendidikan Islam dan Pembelajaran Bahasa Arab di Dayah Darussalam SMK ASD Bireuen, Aceh - Mumtazul Fikri (DAYAH: Journal of Islamic Education, 2023)
Dayah is a progressive educational institution in Aceh that constantly to adapt and adjust to developments in education. Lately, the development of dayah education is entrepreneurship with its peculiarities and characteristics. This research aims to determine the model of Islamic education and Arabic Language learning in Dayah Entrepreneur Darussalam SMK ASD. This research is a qualitative approach with the case study method. Data collection process using interviews, observation and documentation. The research subject is the dayah leader, vice headmaster of curriculum, Arabic teacher and students. Analysis of the research data using data analysis techniques Miles and Huberman with data collection, data reduction, data presentation and drawing conclusions. The results of the reseacrh show that the application of Islamic education in Dayah Entrepreneur Darussalam uses an integrative curriculum. The collaboration and integration between the Vocational High School curriculum into the Islamic boarding school education curriculum. The curriculum integration model used is the across several disciplinary integration model. Learning Arabic at Dayah Entrepreneur Darussalam SMK ASD uses a boarding school educational model with the characteristics of a conservative boarding school. The Arabic material presented is integrated into the teaching of the kitab kuning text. The problems of learning Arabic at Dayah Entrepreneur Darussalam ASD Vocational School, lack of native speakers teaching Arabic, lack of focus in daily Arabic conversation (muhadatsah) and students unable to read the kitab kuning in learning Arabic. The solution is published a concise edition of the Matan Taqrib kitab for the convenience of students to understand Fiqh as well as Arabic. Launched Arabic and English week with rewards and punishments and inviting teachers from Middle East alumni as substitutes for native Arabic speakers.